1990
DOI: 10.2134/jeq1990.00472425001900010001x
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Nitrogenous Fertilizers Applied to Turfgrass

Abstract: Maintaining high quality surface and groundwater supplies is a nntional Concern. Nitrate is a widespread contaminant of groundwater. Nibogenous fertilizer applied to turfgrass could pose a threat to groundwater quality. However, a review of the fate of N applied to turfgrass is lacking, but needed in developing management systems lo minimize groundwater contamination. The discussion of the late o i N applied io iurfgsrass is developed around plant uptake, atmospheric loss, soil storage, leaching, and runoff. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
208
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(223 citation statements)
references
References 13 publications
12
208
2
1
Order By: Relevance
“…The higher soil carbon content in the lawns surveyed, with the greater soil N content (r 2 ϭ 0.86) is supportive of the fact that soil quality may affect the amount of fertilizer that is applied to residential lawns. Further, Petrovic (1990) occurs within the first 10 years of turfgrass establishment. The age of development within the subdivisions with the lower soil N content and higher application rates of fertilizer were less than 10 years old at the time of this survey.…”
Section: Nitrogen Input In Watersheds From Residential Lawn Care 751mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher soil carbon content in the lawns surveyed, with the greater soil N content (r 2 ϭ 0.86) is supportive of the fact that soil quality may affect the amount of fertilizer that is applied to residential lawns. Further, Petrovic (1990) occurs within the first 10 years of turfgrass establishment. The age of development within the subdivisions with the lower soil N content and higher application rates of fertilizer were less than 10 years old at the time of this survey.…”
Section: Nitrogen Input In Watersheds From Residential Lawn Care 751mentioning
confidence: 99%
“…Plot-scale studies have shown that nitrate in run-off from fertilized turfgrass is not necessarily a constant source of nutrients to surface water but is temporally variable. For example, field studies have found low concentrations of nitrate in storm run-off from fertilized lawns (Petrovic, 1990;Garn, 2002), with the exception of storm events after fertilizer applications (Kelling & Peterson, 1975). For example, Line et al (2002), working in suburban sites in North Carolina, measured nitrogen concentrations to be four times higher in run-off from single family residential land uses during February compared to fall or winter concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive N inputs to lawns may enter groundwater as ammonium (NH 4 ? ) and nitrate (NO 3 -, Jiao et al 2004;Petrovic 1990) through leaching, causing threats to public health (Scanlon et al 2007), or enter the atmosphere through ammonia (NH 3 ) volatilization (Torello et al 1983) and emissions of nitrous oxide (N 2 O) and nitrogen monoxide (NO) in nitrification and denitrification (Bouwman et al 2002;Clayton et al 1997;Eichner 1990;Firestone and Davison 1989;Townsend-Small et al 2011). Kaye et al (2004) showed that urban lawns occupied 6.4 % of their study region of urban soils (including urban impervious, urban lawns, agricultural land, and native grassland) but contributed 30 % of the regional emissions of N 2 O, which is a powerful greenhouse gas (IPCC 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Although the amount of rain can be high in some events as in August 8, 2006 (140 mm), the amount of generated runoff wasn't significant (57.6 m 3 ha −1 ) due to low rainfall intensity in addition to the effect of grass filters of reducing runoff velocity and increase infiltration. Petrovic (1990) and Erickson et al (2001) reported that little runoff was generated from turf grass surfaces compared to other land covers under natural precipitation. Heavier rainfall usually translates into more impact on the soil surface resulting in larger amounts of sediment being dislodged and carried away with runoff water.…”
Section: Resultsmentioning
confidence: 99%